Manipulation of cysteine cathepsins during Mycobacterium tubersulosis infection of human macrophages - Pombo, João Palma Neves, 1989- (2014)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2013